Analysis of Students Misconception in Completing Mathematical Questions Using Certainty of Response Index (CRI) - Waluyo, Elsa Meriani; Muchyidin, Arif; Kusmanto, Hadi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The misconception is a notion of an understanding that is inconsistent with a scientific notion or an interpretation of the relationship of unacceptable concepts. This study conducted to identify the misconception of students of class VIII MTs Negeri 9 Cirebon on the concept of a tangent circle. The research method used is a mixed method. Sampling using random sampling, so that obtained 48 student samples. The instruments used in this study were multiple choice objective tests accompanied by Certainty of Response Index (CRI) method and diagnosis interview. Based on its completeness, the analysis shows that misconceptions appear on sub concepts tangent of the circle of 34,5%, a tangent to two circles of 35,6%, an outer circle and an inner circle of the triangle of 33,3%. On average misconceptions that occur in students that are at sub concepts, tangent two circles on about ten percentage are 43,8%. This analysis shows that misconceptions in the student because students do not understand the concept fully and connecting one concept to another with partial understanding, resulting in the student, makes the wrong conclusions. Based on analysis of these data showed that the CRI effectively used to determine the misconceptions and effective diagnostic interview used in knowing the reason students are causing students had misconceptions.